An Investigation On The Performance And Emission Of Gas Turbine Running On Syngas - Hassan, Ahsham (2018)
The increase in global energy demand which coincided with the fossil fuels combined with the reports of global warning and climatic changes has garnered an interest in researches and developers to bring forth alternative sources of energy as well as develop alternative fuels in order to substitute fossil fuel in the short term as well as in the long term to tackle these issues. Power generation is the largest industry in the world which uses fossil fuel to generate electricity by using engines, one such engines used in power generation is the gas turbine which is mainly run on fossil fuels. Due to the government initiatives on emission and mostly due to the increase in concern for global warming the industry has been doing extensive studies on using alternative fuel to run the gas turbines. One such alternative fuel is the syngas. In the paper, a background on gas turbine. One such alternative fuel is the syngas. In this paper, a background on gas turbine and syngas is provided together wit a review of recent studies and development in the gas turbine industry. The focus is on analyzing the performance gas turbine run on syngas by using previously publishes studies and to use this data to create mathematical model for prediction purpose using MATLAB and validate using experimental data obtained from literature